Synthesis of Metastable Ternary Pd-W and Pd-Mo Transition Metal Carbide Nanomaterials - James M. Thode (MDPI AG, 2021)
Research and catalytic testing of platinum group transition metal carbides have been extremely limited due to a lack of reliable, simple synthetic approaches. Powder samples have been reported to phase separately above 1%, and only thin-film samples have been reported to have appreciable amounts of precious metal doping. Herein, we demonstrated, through the simple co-precipitation of Pd and W or Mo precursors and their subsequent annealing, the possibility to readily form ternary carbide powders. During the investigation of the Pd-W ternary system, we discovered a new hexagonal phase, (PdW)2C, which represents the first non-cubic Pd ternary carbide. Additionally, the solubility of Pd in the Pd-W-C and Pd-Mo-C systems was increased to 24 and 32%, respectively. As a potential application, these new materials show an enhanced activity for the methanol oxidation reaction (MOR) compared to industrial Pd/C.